IMPROVING STUDENTS’ READING COMPREHENSION THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION TECHNIQUE TO THE EIGHT GRADE STUDENTS OF SMP SWASTA KATOLIK BUDI MURNI 1 MEDAN - Damanik, Rostani; Pangaribuan, Jontra J.; Ginting, Fiber Yun A. (Kairos English Language Teaching Journal, 2020)
Reading is not only about pronouncing written words correctly but also comprehending the text. It is not surprising the students have difficulties in reading comprehension because they do not understand the language. Therefore the teacher must try to help the students comprehend the text. One thing the teacher can do is to find a technique to teach this reading comprehension. Cooperative Integrated Reading and Composition can help the students to improve their reading comprehension and to arouse their motivation. The aim of this study is to find whether Cooperative Integrated Reading and Composition Technique works effectively on improving students’ reading comprehension and to know what students’ responses after being taught by using this technique. The subject of this study is the eighth grade students of SMP Swasta Katolik Budi Murni 1 Medan in the Academic Year of 2018/2019 were consist 25 students of class VIII C. This study was conducted by applying Classroom Action Research (CAR), which was performed in two cycles ( cycle I and cycle II). The instruments of collecting data were Quantitative data (reading comprehension test) and and qualitative data (field notes,obervation sheet,questionnaire)The result of reading comprehension tests showed that the mean of the students’ score increased from pre-test (20 %), formative test (52 %), post-test (76 %). The field notes, observation sheet and questionnaire showed that the students are interested in the learning teaching process through CIRC Technique and this study run well. It was found that this technique could improve students’ reading comprehension. It is suggested that English teacher should apply this technique in teaching reading comprehension.